Analisis Informasi Perancangan Proses Bisnis Barang Masuk dan Barang Keluar PT. Telkom Regional 1 Sumatera - Triase, Triase; Pasaribu, Afifah Balqis; Ayu, Kartika Dara (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
PT Telekomunikasi Indonesia Tbk was chosen because it is the largest telecommunications company in Indonesia and in accordance with the researcher's study program, namely Information Systems. The results of practical work show that PT Telkom Regional 1 Sumatra still records goods manually which results in difficulties in finding and managing inventory data. The business process of incoming goods and outgoing goods experiences several obstacles, especially in the efficiency of delivery time. Therefore, researchers recommend an improvement plan by combining goods in one shipment and using a larger container, as well as utilizing bubble wrap for the safety of goods. The implementation of these changes is expected to reduce the delivery process time and increase customer satisfaction. In addition, suggestions for the development of an application for ordering goods and monitoring shipments are also proposed to facilitate consumers and improve the efficiency of reporting goods data. Thus, PT Telkom Regional 1 Sumatra can design and create a goods data collection information system to improve business processes that occur in the company.